URGENCY OF FINANCIAL RATIO SCREENING REGULATION FOR MSMEs CO-FUNDING ON SECURITIES CROWDFUNDING SERVICE - Ulum, Kefi Miftachul; Adi Surya Fathoni; Lia, Lia Wilda Izzati (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2025)
As of May 7, 2024, the securities crowdfunding cycle has facilitated the funding of 356 securities, comprising 231 equity securities, 20 debt securities, and 105 sukuk securities. Sukuk experienced an increase in the share of sharia securities funding with a percentage of 30%, up from 22% in 2023. This increase in funding was not accompanied by a specific, legally binding screening standard for sharia securities issuers in the securities offering mechanism. Financial Services Authority or Otoritas Jasa Keuangan (OJK) Regulation Number 35 of 2017 cannot be legally applied as a screening standard for this funding. This research employs a library research methodology with a socio-legal approach to examine this regulatory void. Primary data consists of OJK Regulation No. 35 of 2017 and OJK Regulation No. 57 of 2020, supported by secondary data on offering mechanisms, funding growth, and relevant literature. The study found a lack of specific regulations governing screening standards (core business and financial ratio) for Sharia securities in the SCF cycle. Currently, guidelines are often informally drawn from OJK Regulation No. 35 of 2017, which is legally inappropriate as it is intended for the public-company setting of the Indonesia Stock Exchange. The findings highlight the need for a specific regulation governing screening standards for securities crowdfunding funding. Adopting an economic approach to legal science, this study proposes the development of a specific OJK Regulation (POJK) that provides clear screening criteria and permanent legal consequences for issuers or publishers who violate the Sharia securities criteria.